Placental microRNA methylome signatures may serve as biomarkers and therapeutic targets for prenatally opioid-exposed infants with neonatal opioid withdrawal syndrome - Radhakrishna, Uppala; Nath, Swapan K.; Uppala, Lavanya V.; Veerappa, Avinash; Forray, Ariadna; Muvvala, Srinivas B.; Metpally, Raghu P.; Crist, Richard C.; Berrettini, Wade H.; Mausi, Lori M.; Vishweswaraiah, Sangeetha; Bahado-Singh, Ray O. (Frontiers in Genetics, 2023)
Epigenetic variations in microRNAs (miRNAs) and their impact on addiction-related processes is a rapidly evolving area of research. To Identify miRNA gene methylation profiles associated with Neonatal Opioid Withdrawal Syndrome (NOWS), we analyzed DNA methylation levels of miRNA-encoding genes using Illumina Infinium Methylation EPIC BeadChip in 96 human placental tissues: 32 from mothers with prenatally opioid-exposed infants who required pharmacologic management for NOWS, 32 from mothers with prenatally opioid-exposed infants that did not require treatment for NOWS, and 32 unexposed controls. The study identified 46 significantly differentially methylated (FDR p-value ≤ 0.05) CpGs associated with 47 unique miRNAs, with a receiver operating characteristic (ROC) area under the curve (AUC) ≥0.75 including 28 hypomethylated and 18 hypermethylated CpGs as potentially associated with NOWS. These dysregulated microRNA methylation patterns may contribute to the pathogenesis of NOWS Our data implicate dysregulation of microRNA methylation as a contributor to the pathogenesis of NOWS. This is the first study to analyze miRNA methylation profiles in NOWS infants and illustrates the unique role miRNAs might have in diagnosing and treating the disease. Furthermore, these data may provide a step toward feasible precision medicine for NOWS babies as well.